2023
DOI: 10.1200/jco.22.01485
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Results and Side Effects of Accelerated Partial-Breast Irradiation Versus Whole-Breast Irradiation for Low-Risk Invasive Carcinoma of the Breast: The Randomized Phase III IRMA Trial

Abstract: PURPOSE The results in terms of side effects vary among the published accelerated partial-breast irradiation (APBI) studies. Here, we report the 5-year results for cosmetic outcomes and toxicity of the IRMA trial. METHODS We ran this randomized phase III trial in 35 centers. Women with stage I-IIA breast cancer treated with breast-conserving surgery, age ≥ 49 years, were randomly assigned 1:1 to receive either whole-breast irradiation (WBI) or external beam radiation therapy APBI (38.5 Gy/10 fraction twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Following the RAPID results, the recently published ASTRO guidelines do not recommend twice-daily APBI with EBRT with respect to toxicity and cosmesis [20]. Consistent with the RAPID study, the IRMA trial, which randomly assigned over 3300 patients to receive twice-daily APBI of 38.5 Gy in 10 fractions or WBI, showed that twice-daily APBI had higher rates of late soft tissue toxicity (2.8% vs. 1%), bone toxicity (1.1% vs. 0%), and adverse cosmesis [21]. The randomized trial by Boutrus et al [22] compared once-daily APBI vs. twice-daily APBI schemes with EBRT (38.5 Gy in 10 fractions) on 113 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Following the RAPID results, the recently published ASTRO guidelines do not recommend twice-daily APBI with EBRT with respect to toxicity and cosmesis [20]. Consistent with the RAPID study, the IRMA trial, which randomly assigned over 3300 patients to receive twice-daily APBI of 38.5 Gy in 10 fractions or WBI, showed that twice-daily APBI had higher rates of late soft tissue toxicity (2.8% vs. 1%), bone toxicity (1.1% vs. 0%), and adverse cosmesis [21]. The randomized trial by Boutrus et al [22] compared once-daily APBI vs. twice-daily APBI schemes with EBRT (38.5 Gy in 10 fractions) on 113 patients.…”
Section: Discussionmentioning
confidence: 97%
“…47 Notably, these studies have 5-year primary end points and rely on ET adherence for a minimum of 5 years, which may not be realistic in many settings. 11,12,48 In the Lumina trial of women 55 years and older treated with ET alone, using careful patient selection including negative SLN biopsy in all patients, Ki67 proliferation index <13.25%, and 83% ET adherence, the 5-year LR rate was 2.3% (95% CI, 1.2 to 4.1). Recurrence data on patients followed in the past 5 years were not provided.…”
mentioning
confidence: 99%